2022
DOI: 10.1002/hed.27148
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of anatomical landmarks for performing an endoscopic transoral nasopharyngectomy

Abstract: Background Performing a nasopharyngectomy via a transoral approach has been reported; however, defining landmarks to facilitate this approach has not been addressed. This study aims to explore anatomical landmarks to aid in performing a nasopharyngectomy via the transoral corridor. Methods An endoscopic transoral nasopharyngectomy was performed on six cadaveric specimens (12 sides). Related anatomical landmarks were defined, and the strategy to preserve the parapharyngeal internal carotid artery (pICA) was exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Technical details of a transoral approach for exposure of the pICA, has been previously described 8,14–16 . An incision was performed at the lateral oropharyngeal wall paramedial to the pterygo‐mandibular raphe.…”
Section: Resultsmentioning
confidence: 99%
“…Technical details of a transoral approach for exposure of the pICA, has been previously described 8,14–16 . An incision was performed at the lateral oropharyngeal wall paramedial to the pterygo‐mandibular raphe.…”
Section: Resultsmentioning
confidence: 99%
“…Endoscopic salvage surgery for recurrent NPC is widely accepted and recognized 6,7 . Previous studies have also suggested a transoral transpalatal approach that can avoid dealing with the pterygoid process, and thus, may help with dissection and protect the parapharyngeal internal carotid artery (ICA) 8,9 . The main surgery for early staged recurrent NPC is nasopharyngectomy around the ET.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Previous studies have also suggested a transoral transpalatal approach that can avoid dealing with the pterygoid process, and thus, may help with dissection and protect the parapharyngeal internal carotid artery (ICA). 8,9 The main surgery for early staged recurrent NPC is nasopharyngectomy around the ET. The conventional endoscopic endonasal surgery often requires a transpterygoid approach to expose the structure around the ET, which is traumatic and time consuming, and identification of the ICA is indefinite.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] With the increased usage of a transoral approach for extirpation of tumors arising in the parapharyngeal space, indications have been gradually expanded. [15][16][17][18] For example, the transoral corridor has been used for resection of tumors arising from the retrostyloid compartment. 14 Moreover, for tumors arising from the parapharyngeal space with an extension into the jugular foramen region or the posterior cranial fossae, the transoral corridor can also provide a rational exposure for lesion extirpation.…”
Section: Introductionmentioning
confidence: 99%
“…In the past two decades, a transoral approach for extirpation of tumors arising from the parapharyngeal space has been gradually accepted and applied in various skull base centers 12–15 . With the increased usage of a transoral approach for extirpation of tumors arising in the parapharyngeal space, indications have been gradually expanded 15–18 . For example, the transoral corridor has been used for resection of tumors arising from the retrostyloid compartment 14 .…”
Section: Introductionmentioning
confidence: 99%